Recent Advances in the Endogenous Brain Renin-Angiotensin System and Drugs Acting on It - Urmila, Aswar; Rashmi, Patil; Nilam, Ghag; Subhash, Bodhankar (Journal of the Renin-Angiotensin-Aldosterone System, 2021)
The RAS (renin-angiotensin system) is the part of the endocrine system that plays a prime role in the control of essential hypertension. Since the discovery of brain RAS in the seventies, continuous efforts have been put by the scientific committee to explore it more. The brain has shown the presence of various components of brain RAS such as angiotensinogen (AGT), converting enzymes, angiotensin (Ang), and specific receptors (ATR). AGT acts as the precursor molecule for Ang peptides—I, II, III, and IV—while the enzymes such as prorenin, ACE, and aminopeptidases A and N synthesize it. AT1, AT2, AT4, and mitochondrial assembly receptor (MasR) are found to be plentiful in the brain. The brain RAS system exhibits pleiotropic properties such as neuroprotection and cognition along with regulation of blood pressure, CVS homeostasis, thirst and salt appetite, stress, depression, alcohol addiction, and pain modulation. The molecules acting through RAS predominantly ARBs and ACEI are found to be effective in various ongoing and completed clinical trials related to cognition, memory, Alzheimer’s disease (AD), and pain. The review summarizes the recent advances in the brain RAS system highlighting its significance in pathophysiology and treatment of the central nervous system-related disorders.